Do government knowledge production and use systems matter for global climate change adaptation tracking? Insights from Eastern Africa - Njuguna, Lucy; Biesbroek, Robbert; Crane, Todd A.; Dewulf, Art; Tamas, P. (Springer, 2023)
National contexts play a critical role in shaping the transposition of international laws and agreements, such as the Paris Agreement. However, the relevance of national contexts when assessing global progress in adaptation to climate change has received little theoretical and empirical attention. To bridge this gap, we conduct a comparative study of government systems for producing and using policy knowledge on the livestock sectors of three Eastern Africa countries. We find distinct features within and between countries, which may explain variations in how adaptation progress is tracked. In particular, our study shows that prevailing administrative structures influence horizontal and vertical coordination, with implications for the flow of knowledge within government. The extent of coordination and the establishment of knowledge production procedures and accountability mechanisms affect the compatibility of the various knowledge streams in each country which, in turn, determines the potential for integrating adaptation tracking across the various administrative units. Our findings suggest that the effectiveness and feasibility of tracking adaptation progress over time and space will depend on the adequacy and successful linkage of tracking programs with existing systems of knowledge production and use. These findings underscore the relevance of a fit-for-context approach that examines how adaptation tracking can effectively be integrated into existing structures and processes while developing strategies for improving knowledge production and use.